Autoantibodies in Autoimmune Liver Disease—Clinical and Diagnostic Relevance - Sebode, Marcial; Weiler-Normann, Christina; Liwinski, Timur; Schramm, Christoph (Frontiers in Immunology, 2018)
Testing for liver related autoantibodies should be included in the workup of patients with hepatitis or cholestasis of unknown origin. Although most of these autoantibodies are not disease-specific, their determination is a prerequisite to diagnose autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) and they are components of the diagnostic scoring system in these diseases. In primary sclerosing cholangitis (PSC) on the other hand, autoantibodies are frequently present, but play a minor role in establishing the diagnosis. In PSC however, data on antibodies suggest a link between disease pathogenesis and the intestinal microbiota. The following review will focus on practical aspects of antibody testing in the three major autoimmune liver diseases AIH, PBC and PSC.